Pelatihan Sertifikasi Ahli Refrigerasi Tingkat 1 Bagi Siswa SMK Negeri 1 Kabupaten Tangerang - Prayudi Suparmin; Nurmiati Pasra; Suhengki Suhengki; Hendri Hendri; Roswati Nurhasanah; Arief Suardi Nur Chairat (Sekolah Tinggi Teknik - PLN, 2019)
In accordance Regulation the Minister of Marine Affairs and Fisheries No /MEN/2011, each ship crew must have certificate competency experts for fish storage refrigeration. Before, participating in the competency test, each participant must possess knowledge and skills according to the competency standards of level 1 refrigerators. Partner activity is SMK Negeri 1 Tangerang Districts, which a study program Refrigeration and Air Conditioning (TPPU). Curriculum design has not yet been studied specifically accordance regulations for Refrigeration Experts KKP. This education and training one the solutions to prepare graduates will take the competency certificate. The training be carried out within 3 (three) days, the material refers to regulation certification of refrigeration regulations level 1 KKP. Training is given in form of theory and practice. The pre-test, post-test and evaluation of feedback from participants. The number of participants of the training as 30 consisted of 4 graduate and 26 students of SMK N 1 class XII, Program Study TPPU. From the pre-test and post results, there was 31.12% increase in knowledge about refrigeration system according to competency standard the AR-1 KKP, and from feedback participant that this training activity positively had impact on increasing the competency and expertise participants